Analyzing Performance Audit Reports of Destination Management Organizations' Actions and Outcome - Woodside, Arch; Sakai, M. (Routledge, 2009)
The present article includes a case study that describes and analyzes three performance audit reports over a 3-decade period for one U.S. State government's destination management organization's (DMO) actions and outcomes. This report extends prior studies (Woodside & Sakai 2001, 2003) that support two conclusions: (a) the available independent performance audits of DMOs' actions and outcomes indicate that frequently DMOs perform poorly and fail to meaningfully assess the impacts of their own actions, and (b) the audits themselves are shallow and often fail to provide information on DMOs' actions and outcomes relating to these organizations largest marketing expenditures. The article calls for embracing a strategy shift in designing program evaluations both by government departments responsible for managing destinations' tourism marketing programs and by all government auditing agencies in conducting future management performance audits. The article offers a “tourism performance audit template” as a tool for both strategic planning by destination management organizations and for evaluating DMOs' planning and implementing strategies.